2017
DOI: 10.1111/joa.12583
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal smooth muscle is required for patterning the enteric nervous system

Abstract: The development of the enteric nervous system (ENS) and intestinal smooth muscle occurs in a spatially and temporally correlated manner, but how they influence each other is unknown. In the developing midgut of the chick embryo, we find that smooth muscle actin (SMA) expression, indicating early muscle differentiation, occurs after the arrival of migrating enteric neural crest-derived cells (ENCCs). In contrast, hindgut smooth muscle develops prior to ENCC arrival. Smooth muscle development is normal in experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…Previous studies have demonstrated that these three cell types, intestinal epithelium, intestinal smooth muscle, and the cells of the enteric nervous system, develop over a similar time frame. Importantly, cells derived from these distinct germ layers provide signals that are critical for one another's differentiation (Fu et al, 2004;Graham et al, 2017;Hao et al, 2016;Mwizerwa et al, 2011;Natarajan et al, 2002;Neunlist et al, 2007;Neunlist et al, 2013;Pietsch et al, 2006;Puzan et al, 2018;Reichenbach et al, 2008;Sukegawa et al, 2000) (Fig. 9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that these three cell types, intestinal epithelium, intestinal smooth muscle, and the cells of the enteric nervous system, develop over a similar time frame. Importantly, cells derived from these distinct germ layers provide signals that are critical for one another's differentiation (Fu et al, 2004;Graham et al, 2017;Hao et al, 2016;Mwizerwa et al, 2011;Natarajan et al, 2002;Neunlist et al, 2007;Neunlist et al, 2013;Pietsch et al, 2006;Puzan et al, 2018;Reichenbach et al, 2008;Sukegawa et al, 2000) (Fig. 9).…”
Section: Discussionmentioning
confidence: 99%
“…EPCs, smooth muscle precursors, and epithelial precursors are intermingled during their development and previous studies have shown that signals among these cell types are critical for proper differentiation of each cell type (Fu et al, 2004;Graham et al, 2017;Hao et al, 2016;Mwizerwa et al, 2011;Natarajan et al, 2002;Neunlist et al, 2007;Neunlist et al, 2013;Pietsch et al, 2006;Puzan et al, 2018;Reichenbach et al, 2008;Sukegawa et al, 2000). To learn whether loss of Uhrf1 disrupts interactions between cells derived from the different germ layers, we focused on EPCs.…”
Section: Genetic Chimeras Reveal That Uhrf1 Functions Both Cell-autonmentioning
confidence: 99%
See 1 more Smart Citation
“…This niche is maintained by intestinal subepithelial mesenchymal cells (ISEMCs), whose functions include the maintenance of the basement membrane and regulation of epithelial cell function via signaling pathways involving VEGF, Wnt, R-spondin, and stem cell factor. Multiple studies have suggested that the presence of myofibroblasts, macrophages, and smooth muscle cells enhance the growth and differentiation of artificial intestinal epithelium ( 56 , 57 , 67 69 ). Various authors have addressed the issue of mesenchymal support by utilizing native mesenchyme.…”
Section: Strategies For the Development Of An Artificial Intestinementioning
confidence: 99%
“…In order for an artificial intestine to function as an autonomous, nutrient absorbing apparatus, it must attain some degree of innate peristaltic activity. To achieve this, various labs have focused on the ability to develop a functional enteric nervous system (ENS) ( 69 , 74 76 ). Pachnis’ group identified (RET+) cells serving as multipotent progenitors capable of inducing colonization of aganglionic bowel with neurons and glia ( 77 ), and Schafer et al published a technique for isolation of neurospheres from the ENS ( 78 ).…”
Section: Strategies For the Development Of An Artificial Intestinementioning
confidence: 99%